Q. 43.6( 25 Votes )

Find the zeros of

Answer :

Let f(x) = 4x2 - 4x - 3

Put f(x) = 0


4x2 - 4x - 3 = 0


4x2 - 6x + 2x - 3 = 0


2x(2x - 3) + 1(2x - 3) = 0


(2x + 1) (2x - 3) = 0



Now, sum of zeroes = 1 =


Product of zeroes


Hence, relationship verified.

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses